REVIEW: TEKNOLOGI PREPARASI PATI NANOPARTIKEL DAN APLIKASINYA DALAM PENGEMBANGAN KOMPOSIT BIOPLASTIK - Maryam Maryam; Anwar Kasim; Novelina Novelina; Emriadi Emriadi (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
The use of starch in the industry is very wide, both in the field of food and non-food. Therefore, to expand its application, starch needs to be modified in the form of starch nanoparticles. Nanoparticle technology will improve starch characteristics as a result; it has low suspension viscosity at relatively high concentrations, and has high binding strength due to a large active surface area. In general, there are three ways of making nanoparticle starch, namely acid or enzymatic hydrolysis, regeneration (precipitation) and mechanical treatment. The purpose of this study was to conduct a journal review relating to the preparation method of starch nanoparticles and their application in the development of bioplastic composites. The development of bioplastics is currently constrained by the results of bioplastic characteristics; both the physical and mechanical properties produced are still low. Nanoparticle technology developed to improve the characteristics with the addition of nano-sized material (nanoparticles) into bioplastic formulas that produce nanocomposites. The problem faced in the development of nanoparticle starch is that the preparation method used is not ready for commercial production. The resulting yield is still low and the process steps are too long. One way to overcome this is to adapt the nanoparticle starch preparation method that is more efficient for the production scale.